The first 10 years of the Trojan Horse defence. (January 2015) - Bowles, Stephen; Hernandez-Castro, Julio
Abstract : Apprehended criminals throughout history have always attempted to put the blame on someone else, a strategy popularly known as a SODDI defence (Some Other Dude Did It). When this defence is used, the act of the crime ( actus reus ) and the guilty mind (mens rea) is blamed on another party. A Trojan Horse Defence (THD) is a type of modern SODDI defence, where the mens rea and actus reus are blamed on a piece of software, known as a trojan. 1 It has now become common for people accused of some computer-related crime to claim that the responsibility lies with malware placed on their machine without their knowledge. This so-called Trojan Horse Defence (THD) was first used a decade ago. In this article, Stephen Bowles and Julio Hernandez-Castro of the University of Kent undertake a timely retrospective with an in-depth and critical literature review plus a detailed look at the peculiarities of many court cases from around the world.